Criminal Space In Household Waste Management - Hidayatulloh, Syarif (Universitas Muhammadiyah Gresik, 2024)
The study of environmental crime is an effort to create a clean and healthy environment. The integration of environmental crime with household waste management shows that law enforcement and sustainable development have an impact on the balance of the ability to advance life by maintaining the rights and obligations between humans and nature. The application of criminal sanctions aims to provide a deterrent effect and encourage the community to be more responsible in waste management. Increasing public awareness of the importance of good waste management, as well as strengthening adequate infrastructure, facilities and laws, are steps that need to be taken to create a cleaner and healthier environment. The results of the study are the answer to the problem of household waste management policy which shows the existence of criminal space so that attention is needed so that the legal system that has been created can run effectively and correctly by prioritizing the principles of justice and equality of law without disturbing the existing environmental ecosystem. The method used is the normative juridical method, namely research that uses laws and regulations as the basis for solving the problems presented. The data collection method used in this study is library research. Meanwhile, the data analysis used is qualitative, namely by describing data in a quality manner in the form of sentences that are orderly, coherent, logical, non-overlapping and effective so that it is easy to interpret and analyze the data.